2018
DOI: 10.1038/s41598-018-25189-y
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine catabolism promotes NADPH oxidase-derived reactive oxygen species (ROS) signalling in KB and yumoto cells

Abstract: Thymidine phosphorylase (TP) is a rate-limiting enzyme in the thymidine catabolic pathway. TP is identical to platelet-derived endothelial cell growth factor and contributes to tumour angiogenesis. TP induces the generation of reactive oxygen species (ROS) and enhances the expression of oxidative stress-responsive genes, such as interleukin (IL)-8. However, the mechanism underlying ROS induction by TP remains unclear. In the present study, we demonstrated that TP promotes NADPH oxidase-derived ROS signalling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…One such source is the pentose cycle, which provides infected cells with antioxidants that are necessary for HIV‐1 latency induction (Shytaj et al , 2020). In this regard, we show upregulation of the interconnected pyrimidine metabolism, which is involved in reactive oxygen species (ROS) production (Tabata et al , 2018). The effects of pyrimidine metabolism might underlie G6PD upregulation, which is observed during late‐productive and latent HIV‐1 infection (Shytaj et al , 2020).…”
Section: Discussionmentioning
confidence: 91%
“…One such source is the pentose cycle, which provides infected cells with antioxidants that are necessary for HIV‐1 latency induction (Shytaj et al , 2020). In this regard, we show upregulation of the interconnected pyrimidine metabolism, which is involved in reactive oxygen species (ROS) production (Tabata et al , 2018). The effects of pyrimidine metabolism might underlie G6PD upregulation, which is observed during late‐productive and latent HIV‐1 infection (Shytaj et al , 2020).…”
Section: Discussionmentioning
confidence: 91%
“…TP is upregulated in many tumors and plays an important role in angiogenesis, apoptosis evasion, invasion, and metastasis, as well as in chemotherapy response [90]. Recently, Tabata and coauthors have revealed that TP activity increases NADPH levels via the pentose phosphate pathway (PPP) which activates NADPH oxidase-dependent production of ROS in cancer cells [6, 91]. Previously, it was shown that the addition of thymidine to a TP-overexpressing bladder carcinoma cell line induces cellular oxidative stress [92].…”
Section: Sources Of Ros Generation and Antioxidant Defense Systemsmentioning
confidence: 99%
“…For antioxidant capacity, we showed that the microbial purine degradation pathway may contribute to an increase in antioxidant capacity by increasing plasma thymidine levels (P mediation = 0.02, Figure 6D). Thymidine catabolism may promote NADPH oxidase-derived reactive oxygen species to induce oxidative stress (Tabata et al, 2018). We also found that a Proteobacteria species Parasutterella excrementihominis may contribute to the decrease in plasma triglyceride by increasing plasma androsterone levels (P mediation = 0.02, Figure 6E).…”
Section: Rmt Alters Phenotypic Changes Of Newborn Calves Through Meta...mentioning
confidence: 61%